1995
DOI: 10.1088/0268-1242/10/12/019
|View full text |Cite
|
Sign up to set email alerts
|

Current-voltage characteristics and barrier parameters of Pd2Si/p-Si(111) Schottky diodes in a wide temperature range

Abstract: Current-voltage characteristics of Pd,Si/p-Si(lIl) Schottky barrier diodes studied over a wide temperature range (60-201 K) are shown to follow a thermionic emission-diffusion mechanism under both the forward and the reverse bias conditions. The barrier parameters as evaluated from the forward I-V data reveal a decrease of zero-bias barrier height (q4bo) but an increase of ideality factor (q) and series resistance (R,) with decrease in temperature. Moreover, the changes in bbO,? and R, become quite significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 24 publications
14
139
0
5
Order By: Relevance
“…By fitting a linear region of the semi-log plots, the SBH φ b and ideality factor n were extracted using the Shockley equation, I = I 0 [exp (qV/nkT) − 1], where q, k, and T are the elementary charge, the Boltzmann constant, and temperature, respectively. Moreover, I 0 is the saturation current given by the relation: 21,22 I 0 = AA * T 2 exp (−qφ b /kT) where A is the contact area and A * = 4πqm * k 2 /h 3 is the effective Richardson constant with m * being the effective electron mass in the semiconductor. In our calculation, the value of m * for Al x Ga 1−x N with Al mole fraction x was calculated by a linear interpolation of the theoretical values for GaN (0.22 m 0 ) and AlN (0.35 m 0 ).…”
Section: Methodsmentioning
confidence: 99%
“…By fitting a linear region of the semi-log plots, the SBH φ b and ideality factor n were extracted using the Shockley equation, I = I 0 [exp (qV/nkT) − 1], where q, k, and T are the elementary charge, the Boltzmann constant, and temperature, respectively. Moreover, I 0 is the saturation current given by the relation: 21,22 I 0 = AA * T 2 exp (−qφ b /kT) where A is the contact area and A * = 4πqm * k 2 /h 3 is the effective Richardson constant with m * being the effective electron mass in the semiconductor. In our calculation, the value of m * for Al x Ga 1−x N with Al mole fraction x was calculated by a linear interpolation of the theoretical values for GaN (0.22 m 0 ) and AlN (0.35 m 0 ).…”
Section: Methodsmentioning
confidence: 99%
“…Schottky diodes play an important role in devices operating at cryogenic temperatures as detectors, sensors, microwave diodes, gates of transistors, and infrared and nuclear particle detectors. [9][10][11] Therefore, analysis of the current voltage (I-V) characteristics of the Schottky diodes at room temperature does not give detailed information about their conduction process, the nature of barrier formation at the interface and interface states. [12][13][14][15][16][17] The temperature dependence of the I-V characteristics allows us to understand different aspects of conduction mechanisms and the calculation of interface states.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the temperature-dependent IV characteristics gives a better understanding of the conduction mechanism and to understand different aspects that shed light on the validity of various processes involved. 9) In the present work, we fabricated the Ti Schottky contact to p-type SOI, and evaluated its electrical properties. Especially, temperaturedependent IV characteristics were performed and it will be shown that based on the assumption of the Gaussian distribution of barrier heights, the inhomogeneities of barrier height at the interface are responsible for the temperature dependency of Schottky barrier parameters of Ti/SOI Schottky contact.…”
Section: Introductionmentioning
confidence: 99%